Stitch-by-stitch - Bull, Jane (New York, N.Y DK, 2012)
Introduces beginners to the basic techniques of knitting, embroidery, crocheting, needlepoint, and patchwork and provides step-by-step instructions for a variety of projects
Includes index
1 13
Keywords: Crocheting -- Juvenile literature; Crocheting; Embroidery -- Juvenile literature; Embroidery; Handicraft -- Juvenile literature; Handicraft; Knitting -- Juvenile literature; Knitting